Borderline Personality Disorder in Alex Michaelides’s The Silent Patient - Daniel Filbert; Yoseph Bavo Agung Prasaja (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This research aims to identify and analyses the symptoms, causes, and effects of Borderline Personality Disorder that appears in Alex Michaelides’s The Silent Patient, especially in the two main characters of Theo Faber and Alicia Berenson. The writer uses the qualitative method and employs the psychological approach to analyses the data. There are nine symptoms of Borderline Personality Disorder namely, extreme mood swings, shifting self-image, emptiness, paranoia and dissociation, unstable relationship, fear of abandonment, tantrums or uncontrolled anger, impulsivity, and suicide and self-harm. Meanwhile, the cause of Borderline Personality Disorder is divided into two, biological factors and environmental factors. Lastly, the effects of Borderline Personality Disorder are classified into four aspects namely, relationship, work or school, law, and physical health. The result of the study suggests that Theo Faber exhibit eight symptoms out of nine excluding tantrums or uncontrolled anger. Meanwhile, Alicia Berenson also exhibiting eight symptoms out of nine excluding fear of abandonment. The environmental factors that caused Borderline Personality Disorder to emerged in Theo Faber is his traumatic childhood of physical abuse by his father. Similarly, Alicia also suffers from traumatic childhood of verbal abuse by his father and aunt. Besides that, she also experiences a car accident and witnessing her mother’s death, and she also experiencing sexual harassment by her husband’s brother. Lastly, the effect of Borderline Personality Disorder found in Theo Faber are relationship, law, and physical health, meanwhile the effect of Borderline Personality Disorder in Alicia Berenson are relationship and law.